‘The tropics make it difficult to mope’: The imaginative geography of Alexander Payne’s The Descendants (2011) - Sánchez-Palencia, Carolina (International Journal of English Studies, 2015)
This paper analyses the cinematic landscape of The Descendants (Payne, 2011) by engaging with Edward Said’s concept of “imaginative geographies” (Orientalism, 1978), a theoretical approach that addresses the interaction between the material and the symbolic in spatial representation. I also draw from Henri Lefebvre (The Production of Space, 1974) to explain how Alexander Payne renders space and subjectivity as mutually constitutive. The Descendants’ powerful analogies between family ties and land ties would illustrate this spatial-subjective system in interesting metaphoric parallels. In a similar vein, Lefebvre’s emphasis on the importance of capitalism in the social construction of spaces helps articulate the film’s discussion of Hawaiian land trade politics and the protagonists’ ambivalent relation to it. This reading of the film can be inserted into the context of contemporary revisitations of the Paradise mythology as inextricably bound to postcolonial questions of ecology, nation and globalization.